Proceedings of the 34th ACM/SIGAPP Symposium on Applied Computing 2019
DOI: 10.1145/3297280.3297539
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting automated planning for efficient centralized vehicle routing and mitigating congestion in urban road networks

Abstract: One of the pivotal challenges presented to urban traffic controllers is the effective utilization of the transport infrastructure, as a result of the growing urbanization and of the increasing number of vehicles.In response to this challenge, here we investigate the use of Automated Planning for reducing congestion and maximizing the exploitation of urban networks, by generating routes for the vehicles navigating through the controlled region. Empirical analysis is performed on four case studies (including map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…We then considered a second scenario, with heavy traffic conditions. To simulate heavy traffic, we assumed that twice the normal amount of vehicles (3,800) are accessing the network over the same 1 hour simulation time. We are again assuming that all the vehicles are connected and are following the re-routing instructions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then considered a second scenario, with heavy traffic conditions. To simulate heavy traffic, we assumed that twice the normal amount of vehicles (3,800) are accessing the network over the same 1 hour simulation time. We are again assuming that all the vehicles are connected and are following the re-routing instructions.…”
Section: Resultsmentioning
confidence: 99%
“…In consequence, two different vehicles might take different routes even though they have identical locations of origin and destination. Leveraging Automated Planning to tackle the problem of intelligent vehicle routing throughout the road network achieved promising results [3,2]. Those techniques approach the problem from centralised perspective, i.e., there is a central urban traffic controller that suggests routes to all the navigating vehicles [11].…”
Section: Introductionmentioning
confidence: 99%
“…Automated planning techniques can be used to in a centralised fashion to generate a plan for multiple vehicles. Preliminary works leveraging automated planning techniques in such a fashion aim for minimising the risk of road congestion [15] or satisfying air quality constraints [16]. The preliminary results presented in those works indicate that using the "global" planning approach is promising (e.g.…”
Section: B Traffic Routingmentioning
confidence: 99%
“…roads might not become congested even in rush hours), although it might not scale well with an increasing number of considered vehicles and/or the size of the road network. We took inspiration from the work of Chrpa et al [15] in terms of leveraging automated planning for intelligent vehicle routing. However, the approach that we present in this paper can perform realtime traffic routing, rather than the offline approach of Chrpa et al Further, we consider a different planning formalism, namely numerical planning, that provides an excellent tradeoff between computational complexity and accuracy of the knowledge models.…”
Section: B Traffic Routingmentioning
confidence: 99%
“…The work of Chrpa et al [6] exploits AI-based automated planning techniques for enforcing air-quality constraints in urban traffic. In a more recent work, Chrpa et al [7], showed that AI-based planning techniques can be used for reducing congestion of a controlled urban region by re-routing vehicles, but their work is at an exploratory stage and can cope only with a very limited number of vehicles.…”
Section: Related Workmentioning
confidence: 99%